GUERRILLA CHILDREN. THE STUDENT STRIKES OF 1980 AT THE TECHNOLOGICAL INSTITUTE OF COSTA RICA - Molina Jiménez, Iván (2018)
In 1980, the Technological Institute of Costa Rica (ITCR) students carried out two strikes in demand of better study conditions and a greater student representation in the decision-making bodies of that institution of higher education. Both conflicts had an extraordinary media impact and led, for the first time in Costa Rican history, a state university to be intervened by the police, and forced the Congress to involve in the conflict. Through an agreement reached by representatives of different political parties, the Congress ordered the ITCR authorities to negotiate with the students and initiate a process that would end in 1982 with a change in the type of governance structure of the ITCR.